2016
DOI: 10.1371/journal.pone.0164990
|View full text |Cite
|
Sign up to set email alerts
|

Movement Demands of Elite Under-20s and Senior International Rugby Union Players

Abstract: This study compared the movement demands of elite international Under-20 age grade (U20s) and senior international rugby union players during competitive tournament match play. Forty elite professional players from an U20 and 27 elite professional senior players from international performance squads were monitored using 10Hz global positioning systems (GPS) during 15 (U20s) and 8 (senior) international tournament matches during the 2014 and 2015 seasons. Data on distances, velocities, accelerations, decelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 45 publications
8
61
4
1
Order By: Relevance
“…Furthermore, when looking at relative meterage, our results showed higher numbers for all positions compared to a northern hemisphere senior international team (FRF: 67.1 vs. 61.1 m.min − 1 , SRF: 70.4 vs. 67.6 m.min − 1 , BRF: 72.4 vs. 69.9 m.min − 1 , HB: 78.5 vs. 77.4 m.min − 1 , C: 76.4 vs. 71.9 m.min − 1 , and OB: 82.4 vs. 70.8 m. min − 1 ) [11]. Whereas our current study found slightly lower figures than all positions from a southern hemisphere Super-15 team [19] with the exception of OB (82.5 vs. 82.5 m.min − 1 ) which may show the reliance on the different tactical roles between the teams.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, when looking at relative meterage, our results showed higher numbers for all positions compared to a northern hemisphere senior international team (FRF: 67.1 vs. 61.1 m.min − 1 , SRF: 70.4 vs. 67.6 m.min − 1 , BRF: 72.4 vs. 69.9 m.min − 1 , HB: 78.5 vs. 77.4 m.min − 1 , C: 76.4 vs. 71.9 m.min − 1 , and OB: 82.4 vs. 70.8 m. min − 1 ) [11]. Whereas our current study found slightly lower figures than all positions from a southern hemisphere Super-15 team [19] with the exception of OB (82.5 vs. 82.5 m.min − 1 ) which may show the reliance on the different tactical roles between the teams.…”
Section: Discussionmentioning
confidence: 94%
“…At the start of season, each GPS-IMU unit was attributed for a given player to avoid any inter-device variability [9] between club and international games. Players were categorized into 6 different positions as per Cunningham et al [11]; front row forwards, FRF (n = 38; props (No. 1 and 3) and hooker; 30.1 ± 4.3 years, 1.86 ± 0.03 m, 116.3 ± 6.6 kg); second row forwards, SRF (n = 29; second rowers (No.…”
Section: Experimental Designmentioning
confidence: 99%
“…6 The assessment of in-game demands provides coaches with an understanding of what is required from players 7 , and helps establish physical standards to work on or towards. 8 Only two studies have attempted to quantify the physical demands of international rugby using Global Positioning Systems (GPS). 5,8 This method allows the measurement of in game movement patterns and velocities, whilst also monitoring these same metrics during training sessions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Only two studies have attempted to quantify the physical demands of international rugby using Global Positioning Systems (GPS). 5,8 This method allows the measurement of in game movement patterns and velocities, whilst also monitoring these same metrics during training sessions. This allows the potential to monitor training with the aim of matching or superseding match-play demands, providing a physical and tactical stimulus 7 likely to positively transfer to competition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation